Physiological response of black pepper (Piper nigrum L.) to deficit irrigation - Spadeto Ambrozim, Clodoaldo (Revista Ciência Agronômica, 2021)
Due to the amount of water used in the agricultural sector, compared to other activities, irrigation must be done carefully and based on knowledge of plant water relations. The aim of this work was to evaluate the physiological behavior of young black pepper plants (Piper nigrum L.), subjected to water defi cit, as well as the potential for recovery after stress. In 5 L pots, the plants were subjected to different irrigation levels (100; 78; 58 and 32% of the control depth), with irrigation management performed by an automatic controller from a water tension sensor in the soil. The following traits were evaluated: leaf osmotic potential (Ψo ), relative water content (RWC), stomatal conductance (gs) and photosynthetic pigments. To evaluate the plants’ recovery capacity, substrate rehydration was performed when about 50% of the plants in a treatment had stomatal conductance (gs) close to zero. The different levels of water defi cit reduced the values of all traits. In the treatment 32%, values of -2.39 MPa for Ψo , 60% for RWC and gs close to zero were observed on the 28 th day of water restriction. After three days of rehydration of this treatment, the recovery of these values was partial, not reaching the values of the treatments 100 and 78%. Black pepper plants showed high susceptibility to water restrictions and low capacity for recovery after stress.